2022
DOI: 10.1155/2022/3709415
|View full text |Cite
|
Sign up to set email alerts
|

Calculation Model and Numerical Validation of Horizontal Capacity of Micropiles with Different Section Forms

Abstract: With the popularized application of micropile for slope reinforcement, there are many kinds of pile section form, such as single steel bar, multisteel bar, and tube. In order to obtain the theoretical calculation model of horizontal capacity of micropiles with different types, numerical simulations for two common conditions, namely, soil-soil and soil-rock, were carried out to study micropile reinforced slope’s deformation and failure regulation. The dominated indicator for micropile horizontal capacity was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…According to the upper bound theorem of kinematic limit analysis, Zeng and Xiao [8] proposed an analytical method to calculate the net thrust of 3 × 3 micropile group and the sliding surface of pile slope under the specified safety factor. In addition, Chao et al, Bian, and Sun et al [9][10][11] have consistently shown that micropile has a good effect on reinforcing slopes.…”
Section: Introductionmentioning
confidence: 97%
“…According to the upper bound theorem of kinematic limit analysis, Zeng and Xiao [8] proposed an analytical method to calculate the net thrust of 3 × 3 micropile group and the sliding surface of pile slope under the specified safety factor. In addition, Chao et al, Bian, and Sun et al [9][10][11] have consistently shown that micropile has a good effect on reinforcing slopes.…”
Section: Introductionmentioning
confidence: 97%